The Effects of Culture and Structure on Strategic Flexibility during Business Model Innovation - BOCK, Adam J. (Institutional Knowledge at Singapore Management University, 2012)
This study uses responses from 107 multinational firms to reveal CEO perceptions of the drivers of strategic flexibility during business model innovation. While the positive effect of creative culture is confirmed, partner reliance reduces strategic flexibility during business model innovation. Further, structural change is disaggregated into efforts that either focus managerial attention on core activities or reconfigure existing activities. CEOs perceive that structural flexibility requires structural simplification while retaining control of non-core functions. We find that the relative magnitude of business model innovation effort moderates the effect of reconfiguration on strategic flexibility. The implications for theories of organizational design and dynamic capabilities are discussed.